(untitled) (Global Journal of Medical Research, 2017)
Background: Bacterial endogenous endophthalmitis (BEE) is uncommon and severe. Few patients who have this disease are initially misdiagnosed. Its victims usually have an underlying disease which predisposes them to infection. Blood and vitreous cultures are the mostfrequently used media of establishing the diagnosis. Staphylococcus aureus, group B streptococci, Streptococcus pneumonia and Listeria monocytogenes are the commonly found Gram positive organisms. The most common Gram negative causative bacteria are Klebsiella spp., Escherichia coli, Pseudomonas aeruginosa, and Neisseria meningitidis. Gram negative organisms are responsible for the majority of cases reported from East Asian hospitals, but Gram positive organisms are more common in the developed world. Apart from being rare, BEE has very little literature and there has not been any publication on it in Northern India emphasizing on its management to the best of our knowledge. To fill in this gap in research, we evaluated the use of systemic antibiotics with intravitreal antibiotics and steroids (SAIAS) and/or pars plana vitrectomy (PPV) in treating patients diagnosed with BEE. Aim: To assess the complication rate and visual outcomes of BEE after the use of SAIAS and/or PPV in a cohort of Indian patients who visited our hospital in Northern India. Material and Method: Records of all patients who were diagnosed with BEE and managed at our hospital from 2007 to 2015 were reviewed retrospectively for visual outcomes and complications. Patients’ demographic data, predisposing medical conditions, ocular features, extraocular manifestation of infection, Gram staining, treatment, best corrected visual acuity (BCVA) before and after treatment, indications for any further surgical procedures and length of follow up were collected and analysed. Results: 31 eyes of 29 patients (19 males and 10 females) were identified. Mean age at presentation was 41.8+ 18 years (range 3 – 81 years) with a mean follow up 11.1+ 22.7 mo